Product Purchase Analysis Using Apriori Algorithm Method at Gigra Wholesale Store: Analisis Pembelian Produk Menggunakan Metode Algoritma Apriori Pada Toko Grosir Gigra - Felix Sianturi; Betha Nurina Sari; Asep Jamaludin (SYSTEMATICS, 2022)
Gigra Grocery Store is a store that sells various basic food products. This Gigra store has experiencedproblems in sales, this research raises the problem that exists in the Gigra store, which is related todata that is increasing day by day. If left alone, the transaction data will only become garbage, onlyserves as an archive and cannot be used for market strategy development. This study uses the AprioriAlgorithm and the help of WEKA tools to find a combination of itemset from sales transaction data atthe Gigra store. The stages of data mining used are Knowledge Discovery In Database (KDD) withstages of data selection, preprocessing or cleaning, transformation, data mining and evaluation. Thefinal result of this research can be used as a reference for the store in marketing strategies to increaseproducts for eating and snack places. to reduce in-store losses